OPTIMIZATION OF THE PRODUCTION OF STEEL WITH NORMABLE SULFUR CONTENT - V. V. Kisilenko; V. P. Onishchuk; D. A. Diudkin; V. Ju. Gunenkov; A. V. Glenchenko; S. V. Terletskij (Литьë и металлургия, 2004)
The offered technology allowed to carry out the transformation aluminate impurities, to prevent the fall of hard sulfide calcium and as a result to exclude tightening of the steel-bowl gate at continuous steel cast with the normed content of sulfur and aluminium.